A bird's‐eye view of reservoirs in the Mississippi Basin tips a need for large‐scale coordination. Issue 1 (14th September 2020) - Miranda, Leandro E.; Coppola, Giancarlo; Hatcher, Hunter R.; Jargowsky, Matthew B.; Moran, Zachary S.; Rhodes, Michael C.
Abstract: Reservoirs are mostly managed at local scales as spatially independent units. A basin‐scale perspective may increase awareness at a broader scope and generate insight not evident at local scales. We examined the array of reservoir attributes and fisheries in the Mississippi Basin to identify management opportunities. The basin is the third largest in the world and includes over 1, 700 reservoirs >100 ha, the most of any river basin. Our bird's‐eye view shows a piecemeal approach where reservoirs are mostly administered at the local level. Basin‐wide or catchment coordination to holistically address problems that recur across the basin is mostly lacking. A basin‐wide coordination arrangement could facilitate various facets of reservoir management. We reviewed governance arrangements in major river basins across the globe and concluded that the basin‐wide administrative layer we encourage for the Mississippi Basin may already exist in some basins but may not be directly applicable everywhere.